Relatório de estágio curricular obrigatório: área de clínica médica de pequenos animais - Biasotto, Taís (My University, 2026)
This paper refers to the Mandatory Curricular Internship Report carried out in the field of Small Animal Medical Clinic at Big Pets Veterinary Medical Clinic, located in the municipality of Feliz, Rio Grande do Sul, Brazil, from January 14, 2026, to April 30, 2026, totaling 422 hours. The internship aimed to provide practical experience in the clinical and hospital routine of small animals, enabling the integration between the theoretical knowledge acquired throughout undergraduate studies and its application in professional practice. During the internship period, activities related to the clinical care of dogs and cats, hospitalization, outpatient procedures, complementary examinations, vaccination, patient monitoring, fluid therapy, medication administration, and monitoring of surgical and emergency procedures were followed. A total of 59 clinical cases and 274 procedures were monitored, involving different organic systems and various diseases commonly observed in veterinary routine practice. Gastrointestinal and tegumentary disorders showed the highest frequency among the monitored cases, followed by genitourinary and oncological alterations. This work also describes clinical cases monitored during the internship, highlighting a case of nasal acinar adenocarcinoma and another of facial discoid lupus erythematosus, both in dogs, emphasizing the importance of complementary examinations and early diagnosis in veterinary medical practice. The mandatory curricular internship significantly contributed to technical-scientific development, improvement of clinical reasoning, decision-making skills, and professional development. Furthermore, it provided a greater understanding of the veterinary hospital routine, the importance of preventive medicine, animal welfare, and the ethical role of veterinarians in facing the different challenges of clinical practice. [resumo fornecido pelo autor]
O presente trabalho refere-se ao Relatório de Estágio Curricular Obrigatório realizado na área de Clínica Médica de Pequenos Animais, desenvolvido na Clínica Médica Veterinária Big Pets, localizada no município de Feliz, Rio Grande do Sul, no período de 14/01/2026 a 30/04/2026, correspondendo a 422 horas. O estágio teve como objetivo proporcionar vivência prática na rotina clínica e hospitalar de pequenos animais, possibilitando a integração entre os conhecimentos teóricos adquiridos ao longo da graduação e sua aplicação na prática profissional. Durante o período de estágio, foram acompanhadas atividades relacionadas aos atendimentos clínicos de cães e gatos, internações, procedimentos ambulatoriais, exames complementares, vacinação, monitoramento de pacientes, fluidoterapia, administração de medicamentos e acompanhamento de procedimentos cirúrgicos e emergenciais. Ao todo, foram acompanhados 59 casos clínicos e 274 procedimentos, envolvendo diferentes sistemas orgânicos e variadas enfermidades observadas na rotina veterinária. As afecções gastrointestinais e tegumentares apresentaram maior frequência entre os casos acompanhados, seguidas pelas alterações geniturinárias e oncológicas. O trabalho também descreve casos clínicos acompanhados durante o estágio, com destaque para um caso de adenocarcinoma acinar nasal e outro de lúpus eritematoso discoide facial, ambos na espécie canina, enfatizando a importância dos exames complementares e do diagnóstico precoce na clínica médica veterinária. O estágio curricular obrigatório contribuiu significativamente para o desenvolvimento técnico-científico, aprimoramento do raciocínio clínico, capacidade de tomada de decisão e desenvolvimento profissional. Além disso, possibilitou maior compreensão da rotina hospitalar veterinária, da importância da medicina preventiva, do bem-estar animal e da atuação ética do médico veterinário frente aos diferentes desafios da prática clínica. [resumo fornecido pelo autor]
Keywords: Medicina veterinária; Clínica médica; Cirurgia veterinária; Animais - Doenças - Tratamento; Medicina veterinária de pequenos animais